Coated, Stabilized Enhanced-Efficiency Nitrogen Fertilizers: Preparation and Effects on Maize Growth and Nitrogen Utilization - Qi, Zenglian; Dong, Yuanjie; He, Mingrong; Wang, Maoying; Li, Yu; Dai, Xinglong (Frontiers in Plant Science, 2021)
Coated, slow/controlled release, or stabilized enhanced-efficiency nitrogen fertilizers (EENFs) are effective in improving nitrogen utilization efficiency (NUE) and crop yield. Better performance is expected from coated, stabilized EENFs where urease and nitrification inhibitors are incorporated in coated fertilizers. In this study, two coated, stabilized EENFs, CSU1 and CSU2, were prepared with natural rubber-modified epoxy resin as coating material. In CSU1, inhibitors were homogeneously distributed in the innermost layer of the coating, whereas in CSU2, inhibitors were sandwiched between urea sprill and the coating. Ammonia volatilization experiment and column leaching experiment showed that compared with conventional urea, NH3 volatilization loss was reduced by 73% and 78% and inorganic N leaching lose was reduced by 14% and 36% from CSU1 and CSU2, respectively. In the pot experiment, maize grain yield of 129.71 and 162.92 g/pot was achieved by CSU1 and CSU2, respectively, 41% and 79%, respectively, higher than that achieved by conventional urea. The NUE, nitrogen fertilizer apparent utilization efficiency, partial factor productivity of applied N, and nitrogen utilization efficiency were 46%, 30%, 46%, and 32%, respectively, higher in CSU1 and 58%, 62%, 58%, and 29%, respectively, higher in CSU2 than in the conventional urea treatment. Compared with CSU1, CSU2 had better agronomic effectiveness with a higher NUE. It is recommended that urease and nitrification inhibitors be sandwiched between urea prill and the coating for preparation of novel, environmentally friendly coated, stabilized EENFs with high agronomic effectiveness, high NUE, and low N loss.